Survey of cold ionospheric outflows in the magnetotail - E. Engwall; E. Engwall; A. I. Eriksson; C. M. Cully; M. André; P. A. Puhl-Quinn; H. Vaith; R. Torbert (Annales Geophysicae, 2009)
Low-energy ions escape from the ionosphere and constitute a large part of the magnetospheric content, especially in the geomagnetic tail lobes. However, they are normally invisible to spacecraft measurements, since the potential of a sunlit spacecraft in a tenuous plasma in many cases exceeds the energy-per-charge of the ions, and little is therefore known about their outflow properties far from the Earth. Here we present an extensive statistical study of cold ion outflows (0–60 eV) in the geomagnetic tail at geocentric distances from 5 to 19 RE using the Cluster spacecraft during the period from 2001 to 2005. Our results were obtained by a new method, relying on the detection of a wake behind the spacecraft. We show that the cold ions dominate in both flux and density in large regions of the magnetosphere. Most of the cold ions are found to escape from the Earth, which improves previous estimates of the global outflow. The local outflow in the magnetotail corresponds to a global outflow of the order of 1026 ions s−1. The size of the outflow depends on different solar and magnetic activity levels.